All Categories:

Quick Contact
09030889003




love

MATHS OBJ:
.1-10:CABABCDDAD
11-20:DCABBADDBC
21-30:BCBCBBDACB
31-40:BBACBBDACD
41-50:CDCBCDBACA

(3b)
Convert 2013four to base ten.
23 02 11 30
(2 x 43) + (0 x 42) + (1 x 41) + (3 x 40)
(2 x 64) + (0 x 16) + (1 x 4) + (3 x 1)

128 + 0 + 4 + 3

135ten

 (12a)
Let X represent Bisi`s age and
Let Y represent Fibi`s age
:- x + y = 29 ———– eqn (i)
Seven years ago
(x – 7) = 2(y-7)
X – 7 = 2y – 14
X – 2y = -7 ————eqn (ii)
To get X and Y; We have ;
From equation (ii)
X = -7 + 2y
Substitute for X in eqn (i)
-7 + 2y + y = 29
3y = 29 + 7
3y = 36; y = 36/3 = 12
Substitute Y = 12 into eqn (i)
x +y = 29
x + 12 = 29; x = 29 – 12 =17
:- their present age are;
X = Bisi —-> 17 years
Y = Fibie —> 12 years

Ondo maths portal

MATHS OBJ:
.1-10:CABABCDDAD
11-20:DCABBADDBC
21-30:BCBCBBDACB
31-40:BBACBBDACD
41-50:CDCBCDBACA

(3b)
Convert 2013four to base ten.
23 02 11 30
(2 x 43) + (0 x 42) + (1 x 41) + (3 x 40)
(2 x 64) + (0 x 16) + (1 x 4) + (3 x 1)

128 + 0 + 4 + 3

135ten

 (12a)
Let X represent Bisi`s age and
Let Y represent Fibi`s age
:- x + y = 29 ———– eqn (i)
Seven years ago
(x – 7) = 2(y-7)
X – 7 = 2y – 14
X – 2y = -7 ————eqn (ii)
To get X and Y; We have ;
From equation (ii)
X = -7 + 2y
Substitute for X in eqn (i)
-7 + 2y + y = 29
3y = 29 + 7
3y = 36; y = 36/3 = 12
Substitute Y = 12 into eqn (i)
x +y = 29
x + 12 = 29; x = 29 – 12 =17
:- their present age are;
X = Bisi —-> 17 years
Y = Fibie —> 12 years

Answers will be posted here